Qudwatuna as a Leadership Model in Education Quality Development - Romlah, Siti; Hamzah, Akhmad Fauzi; Makhzuniyah, Minhah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the implementation of educational quality management at MA Dalwa, which is located in the Darullughah Wadda'wah Raci Bangil Islamic Boarding School. Using a qualitative approach and case study design, this study explores the application of the "Qudwatuna" leadership model, which is oriented towards exemplary behavior in developing educational quality. Data collection was conducted through interviews, observations, and documentation, with data analysis techniques employing the Miles and Huberman interactive model. The results of the study indicate that the implementation of educational quality management at MA Dalwa includes strict student recruitment, improving the quality of teaching staff through ongoing training, providing adequate facilities and infrastructure, transparent financial management, and systematic evaluation of educational quality. The Qudwatuna leadership model emphasizes the importance of leaders as role models for the entire academic community, both in academic and moral aspects. A holistic approach that encompasses academic, religious, and practical skills produces graduates who are competent and possess strong character. MA Dalwa's success in enhancing the quality of education can serve as a model for other Islamic educational institutions, particularly in Islamic boarding school settings. This study contributes to the development of quality management models in Islamic boarding schools, particularly in implementing a continuous improvement system and exemplifying leadership based on Islamic values and modern management principles.